Evaluation of the Performance of Sustainable Irrigation Systems in Tertiary Networks in the Lamasi Kanan Irrigation Area, Luwu Regency - Natsar Desi; Andri Andi Nyiwi; Muh. Chaerul; Abri Hadi (Jurnal Penelitian Pendidikan IPA, 2025)
Sustainable irrigation management plays a crucial role in supporting efficient and environmentally friendly agriculture. This study aims to identify the existing condition of the irrigation network, analyze the performance index of the tertiary irrigation system, and explain the concept of sustainable irrigation management in the Lamasi Irrigation Area. The study was conducted at Lamasi Dam, Batusitanduk Village, Walenrang Sub-district, Luwu Regency, using a quantitative descriptive approach. Secondary data were obtained from maps and irrigation network schemes of the Public Works Department of South Sulawesi Province, while primary data were collected through field surveys related to the physical condition of irrigation channels and structures. Performance analysis used irrigation performance index indicators and the ePAKSI application. The results showed a reliable discharge of 10 m³/second with 78 water user farmer associations. Irrigation performance was classified as good with a value of 84.83%, while the tertiary irrigation network condition index was 73.30% (moderate category) as found in this study, with a damage level of 21–40% requiring regular maintenance. The conclusion indicates the need for improved network maintenance and strengthening collaboration between stakeholders based on information technology.